Current Status of Spinal Cord Regenerative Therapies: A Review - Mansoori, Nasim; Bansil, Rohit; Sinha, Sumit (Indian Journal of Neurosurgery, 2016)
Spinal cord injury (SCI) is any injury resulting from an insult to the spinal cord that disrupts its major functions, either completely or incompletely, and it can be caused by both traumatic and nontraumatic events. The number of SCI patients has been continuously increasing due to increasing number of motor vehicles and average age of patients is constantly decreasing. After SCI, nerve cells located at the injured site are severely damaged and eventually die, and these dead cells are cleared away by the immune system and in turn a cavity remains. Unfortunately, till date no effective treatment strategy exists ensuring functional recovery after SCI. There is an imperative need for the development of therapies to reduce the enormous physical and financial burdens of people afflicted with SCI. The surgical treatment has been known to aid in rehabilitation, but cannot substantially improve neurologic and functional outcome after SCI. The stem cell–based therapy has been proposed as a promising treatment strategy for SCI. Many of the current strategies for treatment of SCI involve replacing the cells lost to injury with cells derived from alternative sources, such as Schwann cells, oligodendrocyte precursor cells, and neural stem cells. This review discusses the present status of various cell-based therapies, which are being used for treating SCI.
Keywords: stem cell; spinal cord; regeneration; trauma; injury